Membangun Jaringan Kerjasama Melalui Budaya Literasi Sekolah di SMP Negeri 2 Sukodono Kabupaten Sidoarjo - Eko Cahyo Prawoto; M. Shoim Anwar; Luluk Isani Kulup (Universitas PGRI Adi Buana Surabaya, 2022)
Literacy is very important in the world of education, for teachers and students. Literacy problems at SMP Negeri 2 Sukodono, Sidoarjo Regency, among others, can be overcome by: increasing literacy knowledge and skills in schools, increasing skills in building collaborative networks through school literacy culture, increasing insight and skills in reading interest in schools, increasing literacy best practice writing in schools, as well as increasing school literacy collaboration with the following models: between teachers in one field of study, inter-teacher across fields of study, between teachers and students, between students and students. Literacy collaboration can also be carried out by the school with parents, companies, publishers, the press, universities, and other stakeholders.